2021
DOI: 10.1016/j.rbms.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Alignment between expectations and experiences of egg donors: what does it mean to be informed?

Abstract: This study evaluated the retrospective perceptions of egg donors regarding information communicated about immediate and long-term risks during the process of becoming an egg donor, and the alignment of that perception with their experiences and expectations of egg donation. Data were collected using an anonymous online survey. Egg donors' demographics, perceptions of being informed about immediate complications and long-term risks, and alignment between their expectations and experiences were analysed. In tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…The importance of timing of information provided on known and unknown risks, for example, was evaluated by egg donors as critical to their autonomy. Egg donors, who undergo an identical procedure as egg freezers, felt that being told about immediate side-effects shortly before getting injections or surgery prevented them from making a different decision about undergoing the procedure (Tober et al 2020, 8). As a gateway to the egg freezing process, informational events play a critical role in initiating informed-consent procedure.…”
Section: Affect and Sociality Of Egg-freezing Eventsmentioning
confidence: 99%
“…The importance of timing of information provided on known and unknown risks, for example, was evaluated by egg donors as critical to their autonomy. Egg donors, who undergo an identical procedure as egg freezers, felt that being told about immediate side-effects shortly before getting injections or surgery prevented them from making a different decision about undergoing the procedure (Tober et al 2020, 8). As a gateway to the egg freezing process, informational events play a critical role in initiating informed-consent procedure.…”
Section: Affect and Sociality Of Egg-freezing Eventsmentioning
confidence: 99%
“…Furthermore, donors who did report knowledge of risks perceived them to be minor, suggesting that they were not aware of more serious complications (i.e., cancer). A recent study by Tober et al (2020) demonstrated that 55% of previous egg donors did not feel well informed about potential long-term complications.…”
Section: Prospect Theory and Anchoring Heuristicmentioning
confidence: 99%
“…Indeed, current evidence demonstrates that donors’ awareness of both short-term and long-term medical risks is far from adequate (Gezinski et al, 2016; Kenney & McGowan, 2010; Tober et al, 2020). A U.S. study with previous egg donors revealed that 20% did not recall being aware of any medical risks, and the majority of participants reported being unaware of potential LTMR such as infertility/subfertility and cancer (Kenney & McGowan, 2010).…”
Section: Neoliberalism and The Egg Donation Industrymentioning
confidence: 99%
“…The storage and use of oocytes taken for clinical/therapeutic reasons or non-medical reasons can be carried out by both public and private institutions or other clinical organization, through egg sharing, voluntary egg donation, and so-called “social freezing” [ 18 ]. According to 2016 data from the Center for disease control and prevention, donated oocytes were used in about 9% of all assisted fertilization procedures with a doubling of the demand for donated oocytes between 2005 and 2016 [ 19 ].…”
Section: Oocyte Preservationmentioning
confidence: 99%